A Review of Climate Change and Mosquito Ecology in Constructed Wetlands: Implications for Urban Sustainability and Public Health - Bin Abd Rahim Muhamad Syafiq; Saad Noor Aida; Genasan Veera Singham A/L K.; Weng Goh Hui; Kamal Nurul Hana Mokhtar; Shaharuddin Syafiq Bin (E3S Web of Conferences)
This study explores the ecology of mosquitoes within constructed wetlands, emphasizing the impact of climate change on their distribution and behaviour. Constructed wetlands are integral to green city initiatives, offering multiple benefits such as water purification, habitat provision, and climate resilience. However, these environments also serve as breeding grounds for mosquitoes, presenting challenges for public health. This paper reviews the ecology of mosquitoes in constructed wetlands, analyzing how climatic factors influence their populations and interactions within these systems. Rising global temperatures, which reached a recordhigh average of 1.45°C last year, are accelerating mosquito development. As temperatures continue to rise, the geographical distribution of mosquito species is shifting. or instance, Anopheles stephensi, a known malaria vector, has spread from its original habitats in Asia and the Middle East into parts of Africa. Additionally, Aedes aegypti’s transmission potential is expected to increase, particularly in South Asia and sub-Saharan Africa, while Aedes albopictus is likely to experience a decline in transmission potential in tropical regions that are becoming too hot for its survival. These findings highlight the need for adaptive strategies in the planning and management of urban wetlands to mitigate public health risks while maintaining their ecological benefits amid ongoing climate change.